Nationalism of History Education: A Perspective on Indonesian History Text Books - Samudra Eka Cipta (IJECA (International Journal of Education and Curriculum Application), 2020)
The journey of the Indonesian Nation has begun since the historical period which means that the Indonesian Nation has begun to recognize the tradition of writing as an effort to record the history of its ancestors. The development of the Indonesian nation continues to experience dynamics in each period. From these dynamics then there is an effort to strengthen and unite the Indonesian Nation through nationalism. Nationalism in Indonesia began in 1901-1920 or known as the Early Period of the Indonesian Movement with the marking of movement organizations both oriented towards education and politics. The history of Nationalism in Indonesia is not limited to the Era of Movement but continues to move today. Historical education was born and departed through the History of the Development of the Indonesian Nation. Of course, in the historiography of the Indonesian people is full of records of the struggle of how the founding fathers of the nation fought to establish the Republic of Indonesia through bloodshed. Certainly the essence of Historical Education is how efforts to increase the values of nationalism are presented in the form of historiography. This research has problem formulation which consists of (1) how is the development of historiography in Indonesia?,(2) how is nationalism related to history textbooks, (3) how is the concrete form of nationalism in historical education?.